Resilience processes of brazilian young people: overcoming adversity through an arts program - Sandro Gomes Pessoa, Alex; Maria Coimbra, Renata; Santina Murgo, Camélia; Van Breda, Adrian; Baker, Alison (Revista Pesquisas e Práticas Psicossociais, 2018)
This paper analyzes aspects of the process of resilience in the lives of young people who are exposed to psychosocial risk in the Brazilian context. The reflections presented are grounded in the experience of a youth service that provides art activities, within a milieu of civic engagement and social participation. Through the use of arts pedagogies, this youth service aims to create emancipatory dynamics and disrupt oppressive social structures for young Brazilians experiencing disadvantage. Using a qualitative approach, namely interviews and a focus group, with six young people who had graduated from the youth service, we identified five themes that were associated with the youths’ resilience and the role of the arts and the youth service in their lives. The findings provide a better understanding of the trajectories of resilience and the contribution of participation in a youth service, as well as the personal significance that arts can provide for young people exposed to vulnerable contexts.